An evolutionary change in telomere sequence motif within the plant section Asparagales had significance for telomere nucleoprotein complexes - Rotková, G; Sklenicková, M; Dvorácková, M; Sýkorová, E; Leitch, A R; Fajkus, J (Cytogenetic and genome research, 2004)
In association with a phylogenetic tree of Asparagales, our previous results showed that a distinct clade included plant species where the ancestral, Arabidopsis-type of telomeric repeats (TTTAGGG)n had been partially, or fully, replaced by the human-type telomeric sequence (TTAGGG)n. Telomerases of these species synthesize human repeats with a high error rate in vitro. Here we further characterize the structure of telomeres in these plants by analyzing the overall arrangement of major and minor variants of telomeric repeats using fluorescence in situ hybridization on extended DNA strand(s). Whilst the telomeric array is predominantly composed of the human variant of the repeat, the ancestral, Arabidopsis-type of telomeric repeats was ubiquitously observed at one of the ends and/or at intercalary positions of extended telomeric DNAs. Another variant of the repeat typical of Tetrahymena was observed interspersed in about 20% of telomerics. Micrococcal nuclease digestions indicated that Asparagales plants with a human-type of telomere have telomeric DNA organised into nucleosomes. However, unexpectedly, the periodicity of the nucleosomes is not significantly shorter than bulk chromatin as is typical of telomeric chromatin. Using electrophoretic mobility shift assays we detected in Asparagales plants with a human type of telomere a 40-kDa protein that forms complexes with both Arabidopsis- and human-type G-rich telomeric strands. However, the protein shows a higher affinity to the ancestral Arabidopsis-type sequence. Two further proteins were found, a 25-kDa protein that binds specifically to the ancestral sequence and a 15-kDa protein that binds to the human-type telomeric repeat. We discuss how the organisation of the telomere repeats in Asparagales may have arisen and stabilised the new telomere at the point of mutation.
Keywords: molekulární evoluce; Guanine; Plant Leaves; DNA, Plant; Humans; Nucleoproteins; chromozomální proteiny, nehistonové; guanin; telomerasa; Cell Nucleus; Magnoliopsida; Chromosomes, Plant; repetitivní sekvence nukleových kyselin; telomery; Evolution, Molecular; buněčné extrakty; liliovité; zastoupení bazí; Telomerase; Liliaceae; buněčné jádro; chromatin; lidé; Base Composition; listy rostlin; Chromatin; Chromosomal Proteins, Non-Histone; Arabidopsis; Scilla; Telomere; Repetitive Sequences, Nucleic Acid; rostlinné proteiny; Cell Extracts; DNA rostlinná; Plant Proteins; chromozomy rostlin; nukleoproteiny